Evaluation of three hemagglutinin-based vaccines for the experimental control of a panzootic clade 2.3.4.4b A(H5N8) high pathogenicity avian influenza virus in mule ducks. Issue 1 (4th January 2023) - Niqueux, Éric; Flodrops, Marion; Allée, Chantal; Lebras, Marie-Odile; Pierre, Isabelle; Louboutin, Katell; Guillemoto, Carole; Le Prioux, Aurélie; Le Bouquin-Leneveu, Sophie; Keïta, Alassane; Amelot, Michel; Martenot, Claire; et al.
Highlights: A single injection of homologous hemagglutinin-based RNA or VLP vaccines reduces HP H5N8 shedding in mule ducklings. A homologous hemagglutinin-based VLP vaccine with high antigen content nearly abrogates respiratory and cloacal shedding. The three evaluated hemagglutinin-based vaccines allow a simple serological DIVA strategy. Abstract: In France during winter 2016–2017, 487 outbreaks of clade 2.3.4.4b H5N8 subtype high pathogenicity (HP) avian influenza A virus (AIV) infections were detected in poultry and captive birds. During this epizootic, HPAIV A/decoy duck/France/161105a/2016 (H5N8) was isolated and characterized in an experimental infection transmission model in conventional mule ducks. To investigate options to possibly protect such ducks against this HPAIV, three vaccines were evaluated in controlled conditions. The first experimental vaccine was derived from the hemagglutinin gene of another clade 2.3.4.4b A(H5N8) HPAIV. It was injected at three weeks of age, either alone (Vac1) or after a primer injection at day-old (Vac1 + boost). The second vaccine (Vac2) was a commercial bivalent adjuvanted vaccine containing an expressed hemagglutinin modified from a clade 2.3.2 A(H5N1) HPAIV. Vac2 was administered as a single injection at two weeks of age. The third experimental vaccine (Vac3) also incorporated a homologous 2.3.4.4b H5 HA gene and was administered as a single injection at three weeks of age. Ducks were challenged with HPAIV A/decoy duck/France/161105a/2016 (H5N8) at six weeks of age. Post-challenge virus excretion was monitored in vaccinated and control birds every 2–3 days for two weeks using real-time reverse-transcription polymerase chain reaction and serological analyses (haemagglutination inhibition test against H5N8, H5 ELISA and AIV ELISA) were performed. Vac1 abolished oropharyngeal and cloacal shedding to almost undetectable levels, whereas Vac3 abolished cloacal shedding only (while partially reducing respiratory shedding) and Vac2 only partly reduced the respiratory and intestinal excretion of the challenge virus. These results provided relevant insights in the immunogenicity of recombinant H5 vaccines in mule ducks, a rarely investigated hybrid between Pekin and Muscovy duck species that has played a critical role in the recent H5 HPAI epizootics in France.